2017
DOI: 10.1021/acs.cgd.7b00352
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Packing Arrangement, Chain Conformation, and Physicochemical Properties of Gemfibrozil Amine Salts

Abstract: Salt formation is used to optimize pharmaceutical properties for carboxylic acid drugs but selection can often be empirical. An extended series of salts of the anti-hyperlipidaemia carboxylic acid drug gemfibrozil was prepared using related series of amine counterions to gain a molecular insight into the impact of crystal packing arrangements on their physicochemical properties. With only a few exceptions, the salts had similar crystal packing motifs. Although there was no discernible relationship between melt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…DSC showed GEM to have a melting point of 60.3 °C. This was a sharp narrow peak similar to that published by Ramirez et al (Ramirez et al, 2017) and Aigner et al (Aigner et al, 2005) who reported a melting temperature of 61.2 °C and 59.3 °C respectively. The single endotherm confirmed the thermal stability of GEM and thus the absence of polymorphism within GEM.…”
Section: Solid-state Analysissupporting
confidence: 87%
See 3 more Smart Citations
“…DSC showed GEM to have a melting point of 60.3 °C. This was a sharp narrow peak similar to that published by Ramirez et al (Ramirez et al, 2017) and Aigner et al (Aigner et al, 2005) who reported a melting temperature of 61.2 °C and 59.3 °C respectively. The single endotherm confirmed the thermal stability of GEM and thus the absence of polymorphism within GEM.…”
Section: Solid-state Analysissupporting
confidence: 87%
“…They observed that the increased capacity for hydrogen bond formation had an influence on the crystal structure of the salt and that the increasing hydrophilicity of the counterion was beneficial in solubility enhancement. Ramirez et al characterised the crystal packing, chain conformation and physiochemical properties of crystalline gemfibrozil amine salts (Ramirez et al, 2017). They observed that the cyclic amine counterions increased the melting point, which correlated with an increase in counterion molecular weight whereas the linear amine counterions had a decrease in melting point with an increasing molecular weight and volume.…”
Section: A Salt Formation Involves An Acid/base Reaction That Involvementioning
confidence: 99%
See 2 more Smart Citations
“…use of buffers or novel excipients (Asare-Addo et al, 2018;Adebisi et al, 2016;Adebisi et al, 2016;Al-Hamidi et al, 2014, 2010a, 2010bAsare-Addo et al, 2015;Nokhodchi et al, 2017Nokhodchi et al, , 2015Nokhodchi et al, , 2005Rabinow, 2004;Stahl et al, 2008;He at al., 2017;Ramirez et al, 2017;Šupuk et al, 2013).…”
mentioning
confidence: 99%